HEALTHY AND CLEAN LIVING BEHAVIOR REVIEWED FROM THE NEUROTICISM PERSPECTIVE AND ENVIRONMENTAL KNOWLEDGE - Nurjana Mansur; Suwirman Nuryadin; Eko Siswono (Program Studi Magister Manajemen Lingkungan, 2016)
This study aims to determine the relationship of environmental knowledge and personality neuroticism with clean and healthy life Behavior in high school students 54 East Jakarta. The results showed that: (1) There was a positive relationship between environmental knowledge and clean and healthy life behavior; (2) There is a positive relationship between the personality of neuroticism and the behavior of clean and healthy life; (3) There is a mutually positive relationship between environmental knowledge and the personality of neuroticism with clean and healthy living behavior; Based on the results of the study concluded that to improve the behavior of clean and healthy life, then knowledge about environment and personality of student neuroticism need to be improved. Evidence suggests that schools play an important role in caring for student health, including environmental, policy and stakeholder engagement, health education sessions, and practical health promotion activities. This finding emphasizes the importance of socialization of clean healthy living at an early age through the integration of learning programs in schools.